Fish Community Structure in Karangkates Reservoir Malang Regency East Java - Damayanti, Dienda Happy; Latuconsina, Husain; Prasetyo, Hamdani Dwi (Agrikan Jurnal Agribisnis Perikanan, 2024)
Karangkates Reservoir is a reservoir formed due to the damming of the flow of the Brantas River and the supply of rainwater, has various benefits as a flood prevention, power plant, water supply for agricultural irrigation needs, for fisheries activities. This reservoir is also utilized by local fishermen for fisheries activities, both capture fisheries and aquaculture activities. This study aims to determine the structure of the fish community which includes diversity, uniformity, dominance and water quality of Karangkates reservoir. This study used a survey method with a sampling technique of "purposive sampling" at four different station locations, which were considered to represent the Karangkates Reservoir. There were 8 species of fish from 3 families, red lohan fish (Amphilophus labiatus) was found the most, diversity index (H') throughout the station ranged from 1.04 - 1.62 with low category, uniformity index (E) 0.75 - 0.83 in high category, and dominance index throughout the station 0.26 - 0.44 in low category. Water quality conditions based on PP No. 22 of 2021 concerning the Implementation of Environmental Protection and Management, in the waters of the Karangkates Reservoir at station II (tourism area) the value of dissolved oxygen does not meet class III water quality standards.